Sulfur nanoparticles synthesis and characterization from H2S gas, using novel biodegradable iron chelates in w/o microemulsion - Deshpande, Aniruddha S.; Khomane, Ramdas B.; Vaidya, Bhalchandra K.; Joshi, Renuka M.; Harle, Arti S.; Kulkarni, Bhaskar D. (Nanoscale Research Letters, 2008)
Sulfur nanoparticles were synthesized from hazardous H2S gas using novel biodegradable iron chelates in w/o microemulsion system. Fe3+-malic acid chelate (0.05 M aqueous solution) was studied in w/o microemulsion containing cyclohexane, Triton X-100 and n-hexanol as oil phase, surfactant, co-surfactant, respectively, for catalytic oxidation of H2S gas at ambient conditions of temperature, pressure, and neutral pH. The structural features of sulfur nanoparticles have been characterized by X-ray diffraction (XRD), transmission electron microscope (TEM), energy dispersive spectroscopy (EDS), diffused reflectance infra-red Fourier transform technique, and BET surface area measurements. XRD analysis indicates the presence of alpha-sulfur. TEM analysis shows that the morphology of sulfur nanoparticles synthesized in w/o microemulsion system is nearly uniform in size (average particle size 10 nm) and narrow particle size distribution (in range of 5-15 nm) as compared to that in aqueous surfactant systems. The EDS analysis indicated high purity of sulfur (> 99%). Moreover, sulfur nanoparticles synthesized in w/o microemulsion system exhibit higher antimicrobial activity (against bacteria, yeast, and fungi) than that of colloidal sulfur.
Keywords: Antimicrobial activity; H2S gas; iron chelates; sulfur nanoparticles; w/o microemulsion

Synthesis and magnetic properties of barium-calcium hexaferrite particles prepared by sol-gel and microemulsion techniques - Jotania, R. B.; Khomane, Ramdas B.; Chauhan, C. C.; Menon, Shamal K.; Kulkarni, B. D. (Journal of Magnetism and Magnetic Materials, 2008)
The preparation of W-type hexaferrite particles with the composition BaCa2Fe16O27 by microemulsion and a stearic acid sol - gel method with and without surfactant has been investigated at various sintering temperatures. The structural and magnetic characteristics have been studied by X-ray diffraction ( XRD), a vibrating sample magnetometer ( VSM), scanning electron microscopy ( SEM), thermogravimetric analysis ( TGA), differential scanning calorimetric ( DSC) and Fourier transform infrared ( FTIR) techniques. The effect of sintering temperature on the properties of BaCa2Fe16O27 hexaferrites has been studied. The value of saturation magnetization ( M-s) depends on types of surfactant used. The sample prepared in the presence of polyoxyethylene ( 20) sorbitan monooleat ( Tween 80) shows low saturation magnetization ( M-s 15.10 emu/g), whereas the other sample prepared in the presence of a surfactant cetyltrimethylammonium bromide (CTAB) exhibits high saturation magnetization (M-s = 24.60 emu/g) compared to the normal sample. (C) 2007 Elsevier B. V. All rights reserved.
Keywords: BaCa2Fe16O27; hexaferrite; magnetic property; Microemulsion; Sol-gel method; surfactant

Sodium-doped lithium zirconate nano squares: synthesis, characterization and applications for CO2 sequestration - Khokhani, Mrinal; Khomane, Ramdas B.; Kulkarni, Bhaskar D. (Journal of Sol-Gel Science and Technology, 2012)
Nano squares of sodium-doped lithium zirconate have been synthesized by a simple citrate based sol-gel method at room temperature in the presence of cetyl trimethylammonium bromide (CTAB) as a surfactant. The structural and morphological properties were investigated by X-ray diffraction (XRD) and Transmission Electron Microscopy (TEM) respectively. XRD analysis of sample calcined at 900 A degrees C for 4 h shows the formation of monoclinic lithium zirconate phase. The TEM shows the interesting morphology of formation of nano squares of sodium doped lithium zirconate sample. The carbon dioxide sorption capacity was carried out by TGA analysis at different high temperatures. It is observed that the sample shows similar to 20 wt% carbon dioxide sorption at higher temperature (650 A degrees C) within 20 min which are better than the known reports.
Keywords: Carbon dioxide; CTAB; Lithium zirconate; Sodium doped lithium zirconate; sol-gel; TEM; XRD